Vibrational Spectroscopy: The Solution for Immediate Medical Diagnosis. (2015) - Barr, Hugh; Old, Oliver; Almond, Max; Kendall, Catherine; Rhys-Lloyd, Gavin; Shetty, Geeta; Hutchings, Joanne; Stone, Nicholas
Abstract: The vibrational spectroscopy analytical methods offer several apparent advantages for immediate and real-time medical diagnosis. They are able detect subtle molecular changes that must be present prior to morphological tissue changes. As well as allowing molecular understanding of a diseases natural history, there are very important patient benefits; in particular as an 'optical biopsy' technique for immediate tissue diagnosis in real-time and thus guide immediate therapy. In addition they can be used as a 'digital staining' assisting the histopathologist in diagnosis; or as an automated process for histopathology classification. At present all cancer diagnostics remains reliant on an individual, or now, more frequently a double reported histopathological opinion. This is subjective, time consuming and expensive; with delay between diagnosis and treatment. Normal tissue is removed as a precaution to be certain that early cancer is not present. The correct diagnosis of very early lesions in a cancer pathway is now depends on consensus opinion from expert panels within a clinical trials situation in view of the problems of incorrect diagnosis. Excisional biopsy risks complications, and is dangerous in vulnerable areas. Agreement between pathologists on the presence of early disease is very variable. The delays to the patient pathway are very distressing and the cost is very substantial for our Health services.